MSME Financing in Indonesia Islamic Banks: Impact of Third-Party Funds, ROA, and FDR - Rahmanisa Aulia Safitri; Mukhtar, Saparuddin; Zahra, Siti Fatimah (Jeksyah: Islamic Economics Journal, 2024)
This research aims to analyze the internal factors of banks that influence the distribution of MSME financing at Sharia Commercial Banks. The internal factors in question are seen in terms of Bank Assets, Profitability, and Liquidity. This point of view is measured by the independent variables, namely Third-Party Funds, Return on Assets, and Financing to Deposit Ratio. This research uses time series data sourced from the Otoritas Jasa Keuangan for the period January 2021 - December 2023. Multiple regression models are used for research that employs more than one independent variable. The parameters of multiple linear regression models were estimated using the ordinary least square (OLS) method. This research analyzed publication data from the Otoritas Jasa Keuangan, covering 13 Sharia Commercial Banks, and data from various relevant journals using Eviews 10. The results of the research and hypothesis testing conducted showed that: First, partially, the Third-Party Funds and Financing to Deposit Ratio variables have a significant positive effect on MSME Financing, while the Return on Assets variable has a nonsignificant negative effect on MSME Financing for Sharia Commercial Banks. Second, simultaneously, Third Party Funds, Return on Assets, and Financing to Deposit Ratio have a significant positive effect on MSME Financing at Sharia Commercial Banks. With these results, it is hoped that this research can contribute to policy or decision making for Sharia Commercial Banks to increase financing to the MSME sector, both working capital financing and investment financing for the MSME sector in Indonesia.